(3HjGf eTcd CMGOjK QShd Gddg Udi Gddg Ydjg hSdes - (3GdWMGhj , CHh LYaQ,J (B321 (3g` s ((3CMeO Hf MSf GdHQGhi s)
(3ChdgG (B:s
(3jHOC HHGH HjGf eTcd eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde eeG ESJOd Hg ZjQ hGMO ef Cgd GdYde Ydi LhGR HjY GdQLd YHOg ef QLd Ydi Cf jYJbg s
(3BNQgG (B:s
(3jfJgi HHGH HjGf eTcd eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ai UdGJg Ydi bJdi CMO HYO ebJdge HKeGfi Sfjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
Keywords: (3GdMOjK h GdeUWdMs